Light Steel Training for Public Education and RAB Calculation using of Roof Calculator Application - Dhony Priyo Suseno; Wahyu Dwi Mardian (Jurnal Suara Pengabdian 45, 2024)
News about the failure of Light Steel construction, for example the roof structure of Light Steel collapsing, makes people hesitate to use it. This is of concern to the HAPI association (Indonesian Applicators Association) because construction failures can be caused by many factors. The purpose of this service is to help people get to know more about Light Steel materials, their advantages and disadvantages, how to apply them, and how to find out the volume of material requirements using roof calculator application so they don't suffer losses when using them. The target of this service is the community, especially around Wonoplumbon Village, Mijen District, where many of the residents are construction workers, and need knowledge of Light Steel applications to improve work competence in the world of construction. The methods used are lectures, questions and answers, and hands-on practice on how to cut, join, install screws, make roof trusses, and make sills with Light Steel materials. After this activity it is hoped that the community will understand more in theory and practice about Light Steel materials.